BUGUNGI KUNDA OILADA BOLALARGA KITOBXONLIK VA O‘QISh MADANIYATINI ShAKLLANTIRIShNING BAZI MASALALARI - Ilyasova, Z.U. (SCIENCE and SOCIETY, 2025)
This article explores the role and importance of the family in shaping reading culture and book interest among children. The study examines both theoretical and practical aspects of how parental modeling, the family environment, and literary works influence children’s reading habits. It outlines methodological and psychological approaches to developing reading culture from an early age. The article also provides practical recommendations for encouraging family-based reading practices.